The influence of the intestinal microflora to the efficacy of Rosuvastatin - Lijun Wang (Lipids in Health and Disease, 2018)
Abstract Background Intestinal microflora has been shown to play essential roles in the clinical therapies of metabolic diseases. The present study is aiming to investigate the potential roles and mechanisms of how intestinal microflora mediates lipid-reduction efficacy of Rosuvastatin. Methods To investigate the correlation between the intestinal microflora and efficacy of Rosuvastatin, we analyzed the diversity of intestinal microflora using PCR-DGGE analysis and 16S rDNA sequencing approaches. Furthermore, we compared the blood lipid levels of rat models with dysbiosis of intestinal microflora and control rats upon the Rosuvastatin administration. Results The diversity of the intestinal flora was obviously decreased upon the antibiotic treatment, this effect could be maintained for 2 weeks after establishment of the models. Importantly, the results from 16S rDNA sequencing demonstrated that the abundance of Lactobacillus and Bifidobacterium was remarkably diminished upon the antibiotic treatment in antibiotic+Rosuvastatin-treated group compared to that of Rosuvastatin-treated group and control group. Correspondently, the lipid-reduction efficacy of Rosuvastatin was significantly compromised. However, the diversity of the intestinal flora was recovered 4 weeks after the antibiotic treatment. Subsequently, the lipid-reduction efficacy of Rosuvastatin was also recovered to level of the control rats treated with Rosuvastatin alone. Conclusion Intestinal flora could play an essential role in mediating the lipid-reduction efficacy of Rosuvastatin.